State Financial Audit Accountability Through Indonesia Audit Board Mechanisms - Hasan Basri; Khusnul Hitaminah; Mohammad Anton Suryadi (Indonesian Journal of Law and Economics Review, 2026)
General Background State financial management requires accountability, transparency, and independent oversight to support good governance. Specific Background In Indonesia, the Audit Board of Indonesia or BPK has constitutional authority to audit the management and accountability of state finances through financial audits, performance audits, and audits with specific objectives. Knowledge Gap Although the legal framework for state financial audits is comprehensively regulated, the implementation of audit recommendations still raises concerns regarding accountability and transparency in public financial governance. Aims This study analyzes the legal framework governing BPK’s state financial audit mechanism and examines its role in supporting accountable and transparent state financial management. Results The findings show that BPK’s authority is firmly regulated in the 1945 Constitution, Law Number 15 of 2004, and Law Number 15 of 2006. These regulations establish BPK as an independent and objective external audit institution. However, implementation remains limited by insufficient follow-up on audit results, weak inter-agency coordination, and inadequate public access to audit information. Novelty This study clarifies the relationship between constitutional audit authority, legal audit procedures, and practical barriers in state financial accountability. Implications Stronger external oversight, firmer follow-up mechanisms, better institutional coordination, and wider public transparency are needed to ensure that BPK audits support clean, transparent, and accountable financial governance. Highlights: The legal framework is constitutionally strong and comprehensive. Recurrent findings indicate weak recommendation enforcement. Coordination and public access remain critical implementation issues. Keywords: Audit Board of Indonesia (BPK), State Financial Audit, Accountability, Transparency, Legal Effectiveness.